MOVEMENTS ENCOURAGED AND MOBILIZED “FROM ABOVE” – COMPARATIVE ANALYSIS OF STATE-SPONSORED MOVEMENTS IN RUSSIA AND SERBIA - Glišin, Vanja; Simić, Savo (Political Review, 2024)
In this article, we analyze the concept, challenges, and reasons for the current unsuccessful implementation of the ruling party’s project called "Movement for the People and the State." First mentioned and presented to the public in September 2022, the project — despite numerous speculations about the President leaving the Serbian Progressive Party and founding a movement that would evolve into a political party or public statements that the project represents a reconciliatory block between the ideologically polarized East and West of Serbia, which would potentially represent the backbone of the Serbian national interest without the involvement of foreign states — remained unrealized even though it was postponed to Vidovdan 2023, and then to September of the same year. The movement was not formed even at the beginning of 2024, leaving room for doubt about its realization. The article aims to examine the intention to create a state movement, which in the period of the modern Serbian multiparty system did not have practical application, but also to determine the causes of its stagnation despite sporadic announcements by state officials about its subsequent formalization. The concept of a state movement represents a novelty in the political landscape of Serbia and, as such, deserves the attention of the academic and broader public regarding the scope for the potential realization of such a project in the future.